Challenges in diagnosing and managing sarcomatoid urothelial carcinoma of the renal pelvis: a case report - Lei, Jian; Zhao, Wei; He, Tao; Huang, Hui; Jian, Huayong; Zhang, Mei; Luo, Xike; Gong, Xiaochuan; Wang, Yan (Frontiers in Oncology, 2025)
Sarcomatoid urothelial carcinoma of the renal pelvis is an extremely rare malignant tumor with a high risk of recurrence and metastasis and a poor prognosis. This case reports a 61-year-old male patient with renal pelvic sarcomatoid urothelial carcinoma who developed extensive lymph node metastasis 26 days after posterior laparoscopic radical nephrectomy for renal carcinoma, and the patient died on the 45th postoperative day, with the cause of death being advanced malignancy of the tumor. This case highlights the rapid progression of sarcomatoid urothelial carcinoma, and sarcomatoid variants should be identified as early as possible, with active multidisciplinary adjuvant therapy and closer follow-up when feasible. Retrospective analysis of this patient’s treatment regimen and admission provides lessons for recognizing and aggressively managing this rare and fatal variant of urothelial carcinoma.